Safety and Immunogenicity of an mRNA-Based Human Metapneumovirus and Parainfluenza Virus Type 3 Combined Vaccine in Healthy Adults. (1st May 2022) - August, Allison; Shaw, Christine A; Lee, Heather; Knightly, Conor; Kalidindia, Shiva; Chu, Laurence; Essink, Brandon J; Seger, William; Zaks, Tal; Smolenov, Igor; Panther, Lori
Abstract: Background: Human metapneumovirus (hMPV) and parainfluenza virus type 3 (PIV3) cause respiratory tract illness in children and the elderly. No licensed vaccines are available. Methods: In this phase 1, randomized, dose-ranging, first-in-human study, the safety, reactogenicity, and humoral immunogenicity of an investigational mRNA-based hMPV and PIV3 combination vaccine, mRNA-1653, were evaluated in healthy adults aged 18–49 years. Sentinel participants (n = 20) received 2 doses of mRNA-1653 (25, 75, 150, or 300 μg) in the dose escalation phase, and participants (n = 104) received 2 doses of mRNA-1653 (75, 150, or 300 μg) or placebo in the dose selection phase; injections were 28 days apart. Results: The most common solicited reactogenicity events were injection site pain, headache, fatigue, and myalgia, the majority of which were grade 1 or 2. A single mRNA-1653 dose increased neutralization titers against hMPV and PIV3 1 month after vaccination compared with baseline. No notable increases in neutralizing antibody titers were observed with escalating dose levels after mRNA-1653, although no statistical inferences were made; a second mRNA-1653 dose had little observable impact on antibody titers. Neutralizing titers through 1 year remained above baseline for hMPV and returned to baseline for PIV3. Conclusions: mRNA-1653 was well tolerated, with an acceptable safety profile and increased hMPV and PIV3 neutralization titers in healthy adults.